Self‐Organisation in Oosterwold, Almere: Challenges with Public Goods and Externalities. (16th March 2017) - Van Straalen, Fennie M.; Witte, Patrick; Buitelaar, Edwin
Abstract: Attention to self‐organisation and spontaneous order in urban development is growing both in academia and in planning practice. One of the current academic discussions centres around the desirability of self‐organisation. This paper evaluates the case of self‐organisation in Oosterwold Almere in the Netherlands — an atypical case as it is a large‐scale experimental project of organic urban development. We analysed how this case deals with traditional welfare‐economic justifications for urban planning by the government. Several challenges of self‐governing communities in dealing with public goods and negative externalities are identified. The case of Oosterwold highlights the continued importance of collective action, both in the provision and management of public goods and services, and in the prevention of free‐rider behaviour and inefficient use of space. In Oosterwold, collective solutions are being established to deal with challenges concerning institutions, common costs, and the liability of replacing the urban planning by the government.